Pressure dependence of Ce valence in CeRhIn5. (14th December 2017) - Brubaker, Z E; Stillwell, R L; Chow, P; Xiao, Y; Kenney-Benson, C; Ferry, R; Jenei, Z; Zieve, R J; Jeffries, J R
Abstract: We have studied the Ce valence as a function of pressure in CeRhIn5 at 300 K and at 22 K using x-ray absorption spectroscopy in partial fluorescent yield mode. At room temperature, we found no detectable change in Ce valence greater than 0.01 up to a pressure of 5.5 GPa. At 22 K, the valence remains robust against pressure below 6 GPa, in contrast to the predicted valence crossover at P   =  2.35 GPa. This work yields an upper limit for the change in Ce-valence and suggests that the critical valence fluctuation scenario, in its current form, is unlikely.